EFFECT OF ANCHOVY (STOLEPHORUS SP.) APPLICATION ON RAT ENAMEL MICROHARDNESS AND APATITE CRYSTAL SIZE: AN IN-VIVO STUDY - Gunawan, Harun A; Puspitawati, Ria; Auerkari, Elza Ibrahim (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The study aimed to investigate the in-vivo effect on the enamel microhardness, apatite crystal changes, and fluorapatite formation after applying acidic anchovy solution on rat teeth. Methods: A total of 16 Sprague-Dawley rats were divided into four groups including the untreated baseline group, demineralized distilled water (control) group, positive control (sodium fluoride) group, and anchovy treatment group. Anchovies were heated, powdered, and diluted with demineralized water to a 5% solution. The test and control solutions were applied to rat mandibular incisors twice daily for 7 days. After exposure, the teeth were subjected to microhardness testing, scanning electron microscopy, and energy dispersive X-ray spectroscopy analysis to examine enamel surface and fluoride retention, and X-ray diffraction (XRD) analysis on fluorapatite formation and changes in apatite crystal size. Results: Anchovy treated specimens showed increase in enamel microhardness to 390±29 Vickers hardness number, decrease in apatite crystal size to 19.14±1.24 nm, higher fluoride retention on enamel (5.88±0.32%), reduction of crystal size, and increase in fluoride retention correlated with increase of enamel surface microhardness. Fluorapatite formation was demonstrated by the increased peaks at 2θ=32.67° and 33.87° in XRD analysis. Conclusion: In-vivo application of anchovy solution on rat enamel surface increased enamel surface microhardness and promoted fluorapatite formation. The applied anchovy solution appears to show a clear beneficial effect as a topical fluoride agent. Keywords: Caries, Apatite, Anchovy, Calcium fluoride, Fluorapatite.